The impact of social responsibility practices on sustainable development in the sports and leisure sectors in the Lithuanian and Turkish context - Švagždienė, Biruta; Atalay, Ahmet; Jasinskas, Edmundas; Andriukaitienė, Regina (Transformations In Business & Economics, 2026)
This study distinguishes between the sectors of the sports and leisure industries and examines  their  characteristic  sustainable  development  processes within  the framework  of social responsibility practices and principles. ln recent years, the growing scale and social influence of sports and leisure activities have increased expectations for these sectors to operate mare responsibly and sustainably . ln this context, the role of social responsibility has become increasingly significant, as sports  and  leisure  organizations   are   progressively   undertaking   initiatives  that  contribute   to environmental protection, community well-being, and ethical governance. This study examines the interaction between corporate social responsibility and sustainable development in the sports and leisure sectors in Turkey and Lithuania. The empirical part of the research is based on qualitative data from semi-structured interviews with 30 experts, including 15 from Turkey and 15 from Lithuania. The sample consisted of sports club and federation managers, academics, and NGO social responsibility managers. The data were analysed through descriptive and content analysis using NVivo 14. The findings show that CSR practices in both countries are mainly associated with environmental awareness, healthy living, social inclusion, community well-being and ethical governance. At the same time, major barriers include insufficient financial resources, limited institutional cooperation, low social responsibility awareness, and weak policy support. The study emphasizes that social responsibility practices in these sectors extend beyond traditional organizational responsibilities and encompass broader contributions to ecological sustainability, social equity, and responsible management. Accordingly, it highlights how sports and leisure organizations integrate ecological initiatives, pramote social inclusion programs, and adopt ethical  business  practices  and  principles  across  their  operational  and  strategic  activities.Furthermore, the research reveals the impact of implementing social responsibility initiatives on sustainable development in the sports and leisure sectors, which involve and influence large groups of people. By examining these dynamics, the study contributes to a better understanding of how responsible management approaches in sports and leisure organizations can support long-term sustainability goals and generate positive environmental and social outcomes. The study demonstrates that CSR contributes to sustainable development not only through environmental practices but also through social equity, community participation, and inclusive govemance in both sectors